Implementasi Akad Murabahah Pembiayaan Kendaraan Bermotor Pada Bank BTN Syariah KC Medan - Isnan Maulidin Pohan; Sri Sudiarti (Fakultas Ekonomi dan Bisnis Universita Labuhanbatu Sumatera Utara Indonesia, 2022)
The purpose of this study was to determine the implementation of the murabahah contract for motor vehicle financing at Bank BTN Syariah Medan branch office. This research is a qualitative research using field research, namely research where the data source is obtained directly in the field. Based on the research conducted, it is concluded that the implementation of the murabaha contract at Bank BTN Syariah KC Medan is slightly different from the implementation that has been determined by the Fatwa of the National Sharia Council (DSN) No.04/DSN-MUI/IV/2000. The difference is in the additional contract in the form of a wakalah contract. This action is taken to minimize risk, because if the bank directly determines the item the customer wants, the risk is a specification mismatch between the item and what the customer wants.